Hydrogen Production from Sugarcane Bagasse Pentose Liquor Fermentation Using Different Food/Microorganism and Carbon/Nitrogen Ratios under Mesophilic and Thermophilic Conditions - Mattiello-Francisco, Luísa; Ferreira, Filipe Vasconcelos; Peixoto, Guilherme [UNESP]; Mockaitis, Gustavo; Zaiat, Marcelo (MDPI, 2024)
Hydrogen is a well-known clean energy carrier with a high energetic yield. Its versatility allows it to be produced in diverse ways, including biologically. Specifically, dark fermentation takes advantage of organic wastes, such as agro-industrial residues, to obtain hydrogen. One of these harmful wastes that is poorly discharged into streams is sugarcane bagasse pentose liquor (SBPL). The present study aimed to investigate hydrogen generation from SBPL fermentation in batch reactors by applying different food/microorganism (2–10 F/M) and carbon/nitrogen (10–200 C/N) ratios under mesophilic and thermophilic conditions. Biohydrogen was produced in all pentose liquor experiments along with other soluble microbial products (SMPs): volatile fatty acids (VFAs) (at least 1.38 g L−1 and 1.84 g L−1 by the average of C/N and F/M conditions, respectively) and alcohols (at least 0.67 g L−1 and 0.325 g L−1 by the average of C/N and F/M conditions, respectively). Thermophilic pentose liquor reactors (t-PLRs) showed the highest H2 production (H2 maximum: 1.9 ± 0.06 L in 100 C/N) and hydrogen yield (HY) (1.9 ± 0.54 moles of H2 moles of substrate−1 in 2 F/M) when compared to mesophilic ones (m-PLRs). The main VFA produced was acetate (>0.85 g L−1, considering the average of both nutritional conditions), especially through the butyrate pathway, which was the most common metabolic route of experimental essays. Considering the level of acid dilution used in the pretreatment of bagasse (H2SO4 (1%), 1.1 atm, 120 °C, 60 min), it is unlikely that toxic compounds such as furan derivatives, phenol-like substances (neither was measured), and acetate (<1.0 g L−1) hinder the H2 production in the pentose liquor reactors (PLRs). Sugarcane bagasse pentose liquor fermentation may become a suitable gateway to convert a highly polluting waste into a renewable feedstock through valuable hydrogen production.
Keywords: batch reactors; C/N ratios; F/M ratios; hydrogen; mesophilic condition; pentose liquor; sugarcane bagasse; thermophilic condition; xylose